ЎҚУВ ЖАРАЁНИНИНГ ТУРЛИ ЖИҲАТЛАРИГА МУЛТИАГЕНТЛИ ТИЗИМЛАРНИНГ ИНТЕГРАЦИЯЛАШУВ БОСҚИЧЛАРИ - Турсынбекова, И.Ж. (SCIENCE and SOCIETY, 2023)
This article discusses the evolutionary process of implementing multi-agent systems in various aspects of the learning process. Based on the described approaches, a new multi-agent model of the learning process is proposed, where the category is introduced by its efficiency. It is proposed to unite all participants in a single information educational environment and thereby manage the educational process.